2014
DOI: 10.1159/000363024
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the Glutamine Transporter Slc38a3 (SNAT3) and Ammoniagenic Enzymes in Obese, Glucose-Intolerant Mice

Abstract: Background/Aims: Uric acid nephrolithiasis is prevalent among patients with type 2 diabetes and metabolic syndrome; it is correlated with an acidic urine and lower urinary ammonium excretion and is likely associated with insulin resistance. Insulin stimulates ammoniagenesis in renal cell lines via increased phosphate-dependent glutaminase (PDG) activity and glutamine metabolism. Ammonium excretion into the proximal tubule is mediated at least in part by the Na+/H+-exchanger NHE3 and in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
(98 reference statements)
1
9
0
Order By: Relevance
“…A host of T2D risk factors, such as smoking, high fat and high carbohydrate diet, high blood pressure, and obesity, were found to establish a more pro-inflammatory immune environment in the individual. Higher concentrations of pro-inflammatory cytokines, including TNF-a, IL-6, IL1b, CCL2, as well as increased kinase activation, were found in the adipose tissues of obese individuals [6][7][8]. In addition, studies have shown that B cells in T2D were found to regulate inflammation through producing pro-inflammatory cytokines such as IL-6 and TNF-a and promote pro-inflammatory T cell functions [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A host of T2D risk factors, such as smoking, high fat and high carbohydrate diet, high blood pressure, and obesity, were found to establish a more pro-inflammatory immune environment in the individual. Higher concentrations of pro-inflammatory cytokines, including TNF-a, IL-6, IL1b, CCL2, as well as increased kinase activation, were found in the adipose tissues of obese individuals [6][7][8]. In addition, studies have shown that B cells in T2D were found to regulate inflammation through producing pro-inflammatory cytokines such as IL-6 and TNF-a and promote pro-inflammatory T cell functions [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…An early study suggested that hyperuricemia is part of the metabolic-syndrome cluster of abdominal obesity, impaired glucose tolerance, insulin resistance, dyslipidemia, and hypertension, thereby resulting in hemodynamic abnormalities [8,9]. However, the precise mechanism is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…After a 15-hour fast (5:00 pm-8:00 am), the mice were injected intraperitoneally with glucose (2 g/kg of body weight). The blood glucose levels at 0, 15, 30, 60, and 120 min were measured using an accurate blood glucose meter (Accu-check Performa, Roche, Germany) [15][16][17][18]. The area under the curve (AUC) was calculated using the trapezoid rule.…”
Section: Intraperitoneal Glucose Tolerance Test (Ipgtt)mentioning
confidence: 99%